2017
DOI: 10.1016/j.mam.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bile acid mediated inflammation in the liver

Abstract: Bile acids are synthesized in the liver and are the major component in bile. Impaired bile flow leads to cholestasis that is characterized by elevated levels of bile acid in the liver and serum, followed by hepatocyte and biliary injury. Although the causes of cholestasis have been extensively studied, the molecular mechanisms as to how bile acids initiate liver injury remain controversial. In this chapter, we summarize recent advances in the pathogenesis of bile acid induced liver injury. These include bile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(130 citation statements)
references
References 112 publications
1
120
0
2
Order By: Relevance
“…89 It is well known that inflammation plays major roles in cholestasis. 90 In BDL-induced obstructive cholestasis, neutrophil infiltration, proinflammatory cytokine over production and oxidative stress are correlated with the severity of cholestatic liver injury. 91,92 Bile acids and/or triterpenoids overdose-mediated inflammation in the biliary tree may contribute to cholestatic liver injury.…”
Section: Tgr5 Activation In Oa Hepatoprotection and Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…89 It is well known that inflammation plays major roles in cholestasis. 90 In BDL-induced obstructive cholestasis, neutrophil infiltration, proinflammatory cytokine over production and oxidative stress are correlated with the severity of cholestatic liver injury. 91,92 Bile acids and/or triterpenoids overdose-mediated inflammation in the biliary tree may contribute to cholestatic liver injury.…”
Section: Tgr5 Activation In Oa Hepatoprotection and Hepatotoxicitymentioning
confidence: 99%
“…91,92 Bile acids and/or triterpenoids overdose-mediated inflammation in the biliary tree may contribute to cholestatic liver injury. 18,19,90 In this regards, chenodeoxycholic acid produced cholestasis by activating the NLRP3 inflammasome through TGR5 downstream signalling F I G U R E 3 The Nrf2/ARE activation in OA-mediated hepatoprotection and hepatotoxicity. Induction of Nrf2 (1) promotes GSH biosynthesis and GSH conjugation; (2) increases in Nqo1 and HO-1 detoxify electrophiles; (3) increases in Phase-2 detoxification conjugation; and (4) increases in the Mrp efflux pumps to eliminate toxic bile acids out of hepatocytes.…”
Section: Tgr5 Activation In Oa Hepatoprotection and Hepatotoxicitymentioning
confidence: 99%
“…Given the liver involvement in their synthesis and transport, the liver is exposed to very high concentrations of bile acids. While their detergent‐like properties help with digestion, leakage and accumulation of bile acids in hepatocytes at higher concentrations may lead to activation of cholangiocytes, causing chronic inflammation, proliferation, apoptosis and subsequently fibrosis . Bile acids are thought to play a key role in the progression of both PBC and PSC.…”
Section: Bile Acid Homoeostasis Signalling Pathways and Targets For mentioning
confidence: 99%
“…Neutrophils express myeloperoxidase, which catalyzes the production of large amounts of hypochlorous acid, which kills liver cells by strong oxidation. Immunohistochemistry confirmed that 3-chlorotyrosine-protein complex staining was positive in hepatic necrotic tissue during cholestasis, indicating that neutrophils in the hepatic necrosis area release highly toxic hypochlorous acid, leading to hepatocyte death (14).…”
Section: The Role Of Neutrophils In Cholestasismentioning
confidence: 76%